Implications of Interior Transformation - Ada Luz Vega Barrios (European Scientific Journal, ESJ, 2017)
This article deals with questions related with the insertion of a health professional in a manicomial context, with the objective of working from the deinstitutialization (desmanicomialization) logic. This is a challenge that gives a glimpse of the implementation of the Healthy Habits Program in one of the wards of a psychiatric hospital. This approach is centered in the user, whose objective is to work “from within towards the outside” and demands a listening of all the voices: that of the user, of her family and those of the teams of the professionals. At the same time, it requires an interdisciplinary commintment with the same mission: the integral attention of the person who suffers his/her mental health. This mode of working turns into a work alive in action which produces intersectorial relations which reflect different intentions. Given these interactions, health work is done in a field of sand where tension reigns as a consequence of struggle in micropolitics. At the same time, there is an awareness of the efforts in creating and sustaining health programs with the perspective of the users´ inclusion in society.